2009
DOI: 10.1111/j.1462-2920.2008.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vibrio cholerae with plankton in coastal areas of Mexico

Abstract: The El Niño event of 1997/1998 provided an opportunity to carry out a field experiment in which the relationship of sea surface temperature and the association of Vibrio cholerae with marine plankton could be assessed in Mexican coastal and estuarine areas. Plankton samples were collected from May 1997 through June 1999. Sites included the Mexican ports of Veracruz, Coatzacoalcos and Frontera in the Gulf of Mexico and Ensenada, Guaymas, Mazatlán, Manzanillo, Acapulco and Oaxaca in the Pacific Ocean. Sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…tonsa was shown to harbor VBNC V. cholerae in estuarine and marine regions in Argentina (68), and these VBNC cells reverted to the pathogenic state under favorable conditions. In estuarine and coastal regions in Mexico, V. cholerae O1 but not O139 strains were positively correlated with A. tonsa (65). Interestingly, V. cholerae was not detected in sewage but only in samples from sewage free environments, supporting the suggestion that natural nonpolluted water is the environmental reservoir of V. cholerae (69).…”
Section: Cholerae O1/o139supporting
confidence: 65%
See 2 more Smart Citations
“…tonsa was shown to harbor VBNC V. cholerae in estuarine and marine regions in Argentina (68), and these VBNC cells reverted to the pathogenic state under favorable conditions. In estuarine and coastal regions in Mexico, V. cholerae O1 but not O139 strains were positively correlated with A. tonsa (65). Interestingly, V. cholerae was not detected in sewage but only in samples from sewage free environments, supporting the suggestion that natural nonpolluted water is the environmental reservoir of V. cholerae (69).…”
Section: Cholerae O1/o139supporting
confidence: 65%
“…These copepods were the dominant species in Chesapeake Bay (67) and were abundant in the Bay of Bengal. Other studies have shown that V. cholerae is often associated with A. tonsa (19,65,68). Although these two copepods both belong to the order Calanoida they have different life cycles and physical properties.…”
Section: Cholerae O1/o139mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is interesting because the classical biotype caused the sixth pandemic before being replaced by the El Tor biotype, which is considered extinct. It was noted that altered El Tor strains replaced the prototype of the seventh pandemic El Tor in Asia (Evins et al, 1995;Nair et al, 2002) and Africa (Lizarraga-Partida et al, 2009;Morita et al, 2008). However, the Haitian ctxB variant of V. cholerae was reported to cause epidemics in Asia and Africa (Bhattacharya et al, 2016;Goel et al, 2008;Naha et al, 2012;Rashed et al, 2012;Talkington et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Biotype CL caused the first six of the seven cholera pandemics recorded between 1817 and 1923 (26), with five of these affecting the American continents. Ever since the first cases were detected in the Americas in the 1830s, endemic cholera continued to be prevalent until 1895 (18).…”
mentioning
confidence: 99%